The relationship between work-life balance and women leadership performance: The mediation effect of organizational culture - Wei Hua, Duan; Hasnaa Nik Mahmood, Nik; Normeza Wan Zakaria, Wan; Cun Lin, Li; Xia Yang, Xia (International Journal of Engineering and Technology, 2018)
The objective of this study is examining the relationship among work-life balance, organizational culture and women leadership performance in China, and testing the conceptual research model connecting those three variables. The model was designed and tested by Partial Least Square (PLS) based on data collected from a survey of 290 available questionnaires. The results confirmed that organizational culture has significant and positive mediating effect on the relationship between work-life balance and women leadership performance in China. The findings indicated that the good relationship between work-life balance and organizational culture would lead to a high women leadership. Therefore, organizational culture and work-life balance play crucial function within women leaders in ChinaÂ Â